The utility of personal wearable data in long COVID and personalized patient care - Elizabeth J. Enichen; Kimia Heydari; Serena Wang; Grace C. Nickel; Joseph C. Kvedar (npj Digital Medicine)
Radin et al.’s recent study on patients with long COVID demonstrates that personal wearable data can provide critical insight into complex conditions. This editorial argues that research insights gained through personal wearables support the integration of personal wearables into healthcare. Challenges in incorporating wearable data in the clinic point towards AI data sorting, data sharing, device interoperability, FDA oversight, and expanded insurance coverage as first steps towards addressing these challenges.